Estimating Willingness-to-Pay with Random Valuation Models: An Application to Lake Sevan, Armenia - Wang, Hua; Laplante, Benoit; Wu, Xun; Meisner, Craig (World Bank, Washington, D.C., 2013)
This paper presents a case study of willingness-to-pay (WTP) estimation using random valuation models. A contingent valuation survey was conducted in Yerevan, Armenia to estimate people's WTP for the protection of Lake Sevan. Three elicitation formats-open-ended, closed-ended, and the stochastic payment card (SPC) approach-were used with split random samples. WTP models with heterogeneous errors were constructed and estimated with the survey data. The SPC approach produces a higher estimation of the mean WTP than both the open-ended and closed-ended approaches, while results from the open-ended and closed-ended elicitation formats are similar. Furthermore, contrary to research findings obtained in the United States, this study finds higher WTP estimations with mail surveys than with personal interviews.